IT-Related Service: A Multidisciplinary Perspective. (August 2013) - Huang, Ming-Hui; Rust, Roland T.
Information technology (IT)-related service is the strategic management of the creation and delivery of service in which information and communication technology (referred to as IT here) plays a substantial role. IT can serve as a facilitator (e.g., facilitates access to customer information and customer communication) or enabler (e.g., enables value cocreation), serves as the context (e.g., mobile phone market or e-commerce), or is itself service (e.g., social networking sites or information goods). There are three essential characteristics of IT-related service—it is information-intensive, customer-centric, and multidisciplinary. IT-related service is information-intensive. The ability to communicate (firm-to-customer, firm-to-firm, and customer-to-customer) anytime, anywhere, and to anyone, is significantly facilitated by the recent technology trends of big data, cloud computing, and mobile and networking platforms. IT-related service is customer-centric. The use of IT, both by firms and by customers, alleviates the common observation that there is a trade-off between customer satisfaction and productivity improvement for service. Customers are able to talk back to firms with their new communication power and firms are better able to cost-efficiently satisfy their customers. The study of IT-related service is thus inherently multidisciplinary involving such fields as marketing, strategic management, computer science/information systems, and operations management/organizational research. The results of the IT-service transformation are that IT blurs the distinction between goods and service; service is becoming more goods-like and goods are acquiring the characteristics of service. The Journal of Service Research special issue on IT-related service brings together all of these elements, and provides rich strategic implications for managers.